Data Structure of Regional Transport Forecast Model - Jan Celko; Marek Drliciak; Igor Ripka (Communications - Scientific letters of the University of Zilina, 2016)
There are several ways to define basic transport relations in an studied area. Generally, the values have to represent relevant and real situation. The quality of data sources is the determining factor of transport forecast quality. The basic purpose of transportation planning and management is to match transportation supply with travel demand, which represents ‘need’. A thorough understanding of existing travel pattern is necessary for identifying and analysing existing traffic related problems. Detailed data on current travel pattern and traffic volumes are needed also for developing travel forecasting/prediction models. The prediction of future travel demands is an essential task of the long-range transportation planning process for determining strategies for accommodating future needs.The transport forecast process estimates the number of vehicles or people that will use a specific transportation facility in the future. The article describes gathering and analysing process of available data for Slovak regions. The mathematical model of forecast transport relations needs a unique form of input data and special computing parameters. The aim of paper is to describe the implementation of the existing data to the transport forecast calculation.The output data, which are evaluated from the forecast transport model, have to describe a real vision of the region development. The sets of function parameters (measurable or unmeasurable) are edited by using different results of surveys that are often complicated and very time-consuming.